2021
DOI: 10.1177/09697764211040742
|View full text |Cite
|
Sign up to set email alerts
|

Multiple geographies of precarity: Accommodation policies for asylum seekers in metropolitan Athens, Greece

Abstract: Since early 2016, in the context of the so-called ‘refugee crisis’, a series of accommodation policies for asylum seekers were developed in Greece under the regime of ‘emergency’, consisting of two pillars: On the one hand, the ‘campisation’ of accommodation in the mainland and, on the other hand, urban apartments. This article sheds light on the uneven geographies of accommodation policies for asylum seekers in metropolitan Athens, by investigating in a complementary way the aforementioned distinct – yet inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Kreichauf (2018) [64] coined the term 'infrastructures of forced arrival' to highlight the stabilization of temporary, enlarged, remotely located, and spatially isolated camps with lowered living standards. Qualitative research in Athens has revealed the detrimental effects of the location and the physical structures of camps on access to basic services and on eroding the liveability and autonomy of asylum seekers [37,64] and is compatible to our quantitative findings.…”
Section: Infrastructures Of Forced Arrival and Peripheral Segregationsupporting
confidence: 86%
See 2 more Smart Citations
“…Kreichauf (2018) [64] coined the term 'infrastructures of forced arrival' to highlight the stabilization of temporary, enlarged, remotely located, and spatially isolated camps with lowered living standards. Qualitative research in Athens has revealed the detrimental effects of the location and the physical structures of camps on access to basic services and on eroding the liveability and autonomy of asylum seekers [37,64] and is compatible to our quantitative findings.…”
Section: Infrastructures Of Forced Arrival and Peripheral Segregationsupporting
confidence: 86%
“…The reception system expanded rapidly to include two types of accommodation infrastructure alongside the implementation of the hot-spot approach in the Aegean islands. On the one hand, Open Temporary Reception Facilities ("Sites") were created in isolated areas in mainland Greece, suburban and peri-urban areas in Athens, which were turned into sites of prolonged displacement [37]. On the other hand, urban accommodation in apartments, hotels, and other buildings in the city of Athens, and other Greek cities, was a social innovation introduced through a specially designed program (ESTIA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duszczyk et al, 2020;Gregurović & Župarić-Iljić, 2018). Recent works on Greece remain limited in covering the complexities of the issues in relation to the crises; they address policy related issues, including those concerning basic needs and work (Afouxenidis et al, 2017;Bagavos & Kourachanis, 2021;Frangiskou et al, 2020;Manou et al, 2021;Papatzani et al, 2022). Chapters 13, 14 and 15 of Part V add to the above literature with fresh perspectives on the perennial integration challenges Greece was faced with during a period of consecutive crises, including the pandemic of Covid-19.…”
Section: Crises and Migration Related Work On Greece: Situating The C...mentioning
confidence: 99%
“…Platts-Fowler and Robinson (2015) found that integration can evolve in distinctive ways in different places because it is grounded and embodied in space and place. Regarding regulated accommodation, uneven geographies increase precarity (Papatzani et al 2021). Kreichauf (2018) argues that accommodation inside camps separates population, excludes migrants spatially and legally, and stabilizes temporality, marking immigrants as a shortterm phenomenon.…”
Section: Research Building Blocksmentioning
confidence: 99%